Site-specific Solid Cancer Mortality After Exposure to Ionizing Radiation: A Cohort Study of Workers (INWORKS). Issue 1 (January 2018) - Richardson, David B.; Cardis, Elisabeth; Daniels, Robert D.; Gillies, Michael; Haylock, Richard; Leuraud, Klervi; Laurier, Dominique; Moissonnier, Monika; Schubauer-Berigan, Mary K.; Thierry-Chef, Isabelle; Kesminiene, Ausrele
Abstract : Background: There is considerable scientific interest in associations between protracted low-dose exposure to ionizing radiation and the occurrence of specific types of cancer. Methods: Associations between ionizing radiation and site-specific solid cancer mortality were examined among 308, 297 nuclear workers employed in France, the United Kingdom, and the United States. Workers were monitored for external radiation exposure and follow-up encompassed 8.2 million person-years. Radiation–mortality associations were estimated using a maximum-likelihood method and using a Markov chain Monte Carlo method, the latter used to fit a hierarchical regression model to stabilize estimates of association. Results: The analysis included 17, 957 deaths attributable to solid cancer, the most common being lung, prostate, and colon cancer. Using a maximum-likelihood method to quantify associations between radiation dose- and site-specific cancer, we obtained positive point estimates for oral, esophagus, stomach, colon, rectum, pancreas, peritoneum, larynx, lung, pleura, bone and connective tissue, skin, ovary, testis, and thyroid cancer; in addition, we obtained negative point estimates for cancer of the liver and gallbladder, prostate, bladder, kidney, and brain. Most of these estimated coefficients exhibited substantial imprecision. Employing a hierarchical model for stabilization had little impact on the estimated associations for the most commonly observed outcomes, but for less frequent cancer types, the stabilized estimates tended to take less extreme values and have greater precision than estimates obtained without such stabilization. Conclusions: The results provide further evidence regarding associations between low-dose radiation exposure and cancer. Abstract : Supplemental Digital Content is available in the text.